Should Math Tools and Quantitative Methods be Part of University-based Translator and Interpreter's Training? Russian Graduates' Voices in the Focus. Issue 8 (2017) - Atabekova, Anastasia; Stepanova, Valentina; Udina, Natalia; Gorbatenko, Olga; Shoustikova, Tatyana
No abstract available